Microtonal techniques in contemporary zheng compositions: New techniques and soundscapes - Zhang Zhan; Lee Chie Tsang Isaiah (Global Academic Excellence, 2024)
Microtones are becoming increasingly prevalent in contemporary zheng signaling a significant shift in the instrument’s musical landscape. This trend is exemplified in five seminal works by Tang Jianping, Qin Wenchen, Zhu Lin, and Chaoming Tung, revealing how specific microtonal techniques redefine the expressive and technical parameters of this traditional Chinese plucked instrument. Unconventional tunings that deviate from the traditional pentatonic scale, alongside left-hand ornamentation such as pitch bending and sliding, and expanded timbral palettes utilizing harmonics and non-standard playing techniques, are central to this transformation. These techniques not only unlock new sonic landscapes but also imbue zheng music with nuanced emotional expression and melodic complexity, thereby transcending the limitations of traditional pentatonicism and equal temperament. The resulting musical language, imbued with microtonal inflections, resonates with contemporary aesthetic sensibilities while expanding the boundaries of traditional Chinese musical expression.